PEMODELAN MATEMATIKA ALIRAN DARAH PADA PEMBULUH DARAH ARTERI DAN VENA PADA KELAINAN JANTUNG SINGLE VENTRICLE - Pradina, Mutia Aris (Kadikma, 2020)
Single ventricle is a heart defect in which one of the ventricle does not developed and bother the blood flow. One of the solutions is fontan surgery. The result of Fontan surgery allows the blood flowing in veins that initially lead to the heart change into the arteries. Because of these changes, there are possibility of swelling and velocity change of blood flowing. This research constructed a mathematical model of blood flowing velocity in arteries and veins due to a single ventricle heart defect that was formed from the momentum and mass equation, which was influenced by the diameter of venous vessel and blood viscosity. The analysis of the blood flow velocity in arteries and veins due to single ventricle heart defect was simulated by MATLAB and FLUENT software. The factors observed were the effect of venous diameter and blood viscosity on the velocity of blood flow in the veins. The result indicated that the greater diameter of the vein, the smaller the flow velocity in the vein. The greater blood viscosity resulted the smaller flow velocity in arteries and veins.